2021
DOI: 10.5114/aoms/141577
|View full text |Cite
|
Sign up to set email alerts
|

Effects of n-3 polyunsaturated fatty acid supplementation on pregnancy outcomes: a systematic review and meta-analysis

Abstract: IntroductionThere are limited studies exploring the effects of n-3 PUFA supplementation on pregnancy outcomes. The goal of this study was to review relevant studies in order to determine the effect of n-3 polyunsaturated fatty acid (n-3 PUFA) supplementation on pregnancy outcomes based on eligible randomized controlled trials (RCTs).Material and methodsQualified studies were searched by keywords in PubMed, the Cochrane library and Embase. Studies from other pertinent sources were also reviewed, and RCTs publis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…When the balance of n-6 PUFAs versus n-3 PUFAs favored the former, a positive correlation was observed with GDM incidence, and preventing GDM by supplementing with n-3 PUFAs has not yet been conclusively demonstrated. Available evidence suggests that n-3 PUFA supplementationis not beneficial in reducing the incidence of maternal pregnancy outcomes such as gestational diabetes and hypertension, but is beneficial for neonatal health, such as reducing the incidence of preterm labor and low birth weight, and increasing birth weight and birth length [ 130 ]. Notably, n-3 FA supplementation in pregnant women with GDM is beneficial to reducing IR and inflammation and decreasing adverse pregnancy outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…When the balance of n-6 PUFAs versus n-3 PUFAs favored the former, a positive correlation was observed with GDM incidence, and preventing GDM by supplementing with n-3 PUFAs has not yet been conclusively demonstrated. Available evidence suggests that n-3 PUFA supplementationis not beneficial in reducing the incidence of maternal pregnancy outcomes such as gestational diabetes and hypertension, but is beneficial for neonatal health, such as reducing the incidence of preterm labor and low birth weight, and increasing birth weight and birth length [ 130 ]. Notably, n-3 FA supplementation in pregnant women with GDM is beneficial to reducing IR and inflammation and decreasing adverse pregnancy outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, Aparicio et al found that fish and seafood consumption during pregnancy increased EPA concentration and reduced the maternal serum n-6/n-3 PUFA ratio and AA/EPA ratio in the first and third trimester of gestation [ 35 ]. Similarly, n-3 PUFA supplementation during pregnancy has been shown to have beneficial effects on neonatal health [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…[23,24] Some studies suggest EPA is ineffective in preventing GDM. [11,14,15] Some studies have shown that EPA can prevent GDM. [17,18] Pregnant women with established GDM can reduce blood glucose, lipids, high-sensitivity C-reactive protein and insulin resistance levels by consuming EPA.…”
Section: Polyunsaturated Fatty Acidmentioning
confidence: 99%
“…[9] Some studies have shown that DHA does not prevent GDM. [10][11][12][13][14][15] Some studies have shown that DHA can prevent GDM. [16][17][18] Meanwhile, prospective clinical studies have shown that DHA increases the risk of GDM.…”
Section: Polyunsaturated Fatty Acidmentioning
confidence: 99%